Kepemimpinan Ketua Yayasan Berdasarkan kecerdasan Emosional (EQ) Di Pondok Pesantren - Aji Imam Hilman (UNISAN JURNAL, 2024)
This exploration intends to portray the authority of the Seat of the Alhauro Islamic Live-in School Instructive Establishment, Majalengka Regime and dissect the point of view of the ability to understand people on a profound level. This exploration was led utilizing perception, interview and documentation procedures. Testing the legitimacy of the information utilizes triangulation methods, which in this examination underscores the wellspring of the triangulation procedure. The source is all residents beginning from the groundwork of a decent board, the climate, individuals around them. This source will contain information about the authority of the Director of the Alhauro Islamic Life experience School Establishment, Majalengka Regime in light of the capacity to appreciate anyone on a profound level. The consequences of the examination show that the Seat of the Alhauro Islamic Life experience School Establishment, Majalengka Regime, has great authority regarding the ability to understand people on a deeper level. The aftereffects of the examination show that the executive of the establishment completes base administration well indeed. This is demonstrated by triangulation of information and sources. The executive of the Alhauro Islamic Live-in School Instructive Foundation, Majalengka Rule, has a high obligation to the vision representing things to come, particularly in the midst of stress or amidst expanding liabilities. The administrator of the establishment adopted a close to home strategy to all establishment individuals. The Establishment Seat can peruse his own feelings and perceive their effect utilizing impulse to direct choices, knows his assets and restrictions, have some control over his feelings and show genuineness and honesty, can be relied upon. The Executive of the Establishment has great mindfulness and self-administration, great social mindfulness and great relationship the board.